‘Bouncing Back’ From Subclinical Malaria: Inflammation and Erythrocytosis After Resolution of P. falciparum Infection in Gambian Children - Mooney, Jason P.; DonVito, Sophia M.; Jahateh, Maimuna; Bittaye, Haddy; Keith, Marianne; Galloway, Lauren J.; Ndow, Mortala; Cunnington, Aubrey J.; D’Alessandro, Umberto; Bottomley, Christian; Riley, Eleanor M. (Frontiers in Immunology, 2022)
Recent malaria infection is associated with an increased risk of systemic bacterial infection. The aetiology of this association is unclear but malaria-related haemolysis may be one contributory factor. To characterise the physiological consequences of persistent and recently resolved malaria infections and associated haemolysis, 1650 healthy Gambian children aged 8–15 years were screened for P. falciparum infection (by 18sRNA PCR) and/or anaemia (by haematocrit) at the end of the annual malaria transmission season (t1). P. falciparum-infected children and children with moderate or severe anaemia (haemoglobin concentration < 11g/dl) were age matched to healthy, uninfected, non-anaemic controls and screened again 2 months later (t2). Persistently infected children (PCR positive at t1 and t2) had stable parasite burdens and did not differ significantly haematologically or in terms of proinflammatory markers from healthy, uninfected children. However, among persistently infected children, IL-10 concentrations were positively correlated with parasite density suggesting a tolerogenic response to persistent infection. By contrast, children who naturally resolved their infections (positive at t1 and negative at t2) exhibited mild erythrocytosis and concentrations of pro-inflammatory markers were raised compared to other groups of children. These findings shed light on a ‘resetting’ and potential overshoot of the homeostatic haematological response following resolution of malaria infection. Interestingly, the majority of parameters tested were highly heterogeneous in uninfected children, suggesting that some may be harbouring cryptic malaria or other infections.